2013
DOI: 10.1007/s00592-013-0459-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between glucose variability as assessed by continuous glucose monitoring (CGM) and diabetic retinopathy in type 1 and type 2 diabetes

Abstract: There is a growing debate in the literature on whether glucose variability contributes, as well as high HbA1c levels and longstanding diabetes, to the onset and progression of diabetic retinopathy (DR) in patients with diabetes types 1 (DM1) and 2 (DM2). Few data, obtained only by self-monitoring of blood glucose, support this hypothesis. We used continuous glucose monitoring (CGM) to investigate the association between DR and glucose variability parameters (SD, CONGA 2, MAGE), acute hyperglycemia (HBGI) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
83
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 32 publications
4
83
3
1
Order By: Relevance
“…Of note, previous reports suggested that acute oscillations of blood glucose have a more deleterious effect on endothelial function than constant hyperglycemia in patients with type 2 diabetes (T2DM) (3,4), which may support the concept that glycemic variability can induce oxidative stress and thereby affect the pathophysiologic pathways through which diabetes complications arise (5). However, although some studies have reported that increased glycemic variability may be associated with the incidence of diabetic retinopathy (6,7), diabetic neuropathy (8), and coronary artery calcification (9) in patients with T2DM and type 1 diabetes (T1DM), other studies have not supported this association (10)(11)(12). Nevertheless, although its relevance to vascular complications remains uncertain (13), at a given level of glycemia, increased glucose variability raises the risk of hypoglycemia (14)(15)(16) and, hence, is clinically important.…”
mentioning
confidence: 87%
“…Of note, previous reports suggested that acute oscillations of blood glucose have a more deleterious effect on endothelial function than constant hyperglycemia in patients with type 2 diabetes (T2DM) (3,4), which may support the concept that glycemic variability can induce oxidative stress and thereby affect the pathophysiologic pathways through which diabetes complications arise (5). However, although some studies have reported that increased glycemic variability may be associated with the incidence of diabetic retinopathy (6,7), diabetic neuropathy (8), and coronary artery calcification (9) in patients with T2DM and type 1 diabetes (T1DM), other studies have not supported this association (10)(11)(12). Nevertheless, although its relevance to vascular complications remains uncertain (13), at a given level of glycemia, increased glucose variability raises the risk of hypoglycemia (14)(15)(16) and, hence, is clinically important.…”
mentioning
confidence: 87%
“…Indeed, other studies have correlated glycemic variability to risk of diabetes complications, notably neuropathy and retinopathy. [23][24][25] Bajaj et al demonstrated reduced glucose variability with basal insulin and GLP-1 RA therapy compared to other insulin-based regimens. 26 In 160 T2D patients with HbA1c £7.5%, using blinded CGM for 6 days, this study showed that basal insulin with GLP-1 RA therapy reduced the standard deviation of daily glucose compared to basal insulin with oral medications, basal/bolus regimen, and premixed insulin regimens (P = 0.03, P = <0.01, and P = 0.01, respectively).…”
Section: Glucose Variabilitymentioning
confidence: 99%
“…64 Data from another study of 68 patients with DM1 and DM2 suggest that glucose variability may constitute a risk factor for diabetic retinopathy, particularly in the context of acute fluctuations and acute hyperglycemia, regardless of HbA1c. 65 As far as nephropathy is concerned, a study of 12,833 individuals without a history of renal disease or diabetes indicated that impaired glucose tolerance, but not isolated impaired fasting glucose, is associated with increased GFR and a higher risk of glomerular hyperfiltration (estimated GFR above the age-and gender-specific 95th percentile for apparently healthy subjects) (OR 1.34, 95%CI: 1.107-1.66, p=0.009).…”
mentioning
confidence: 99%